Business metadata: Representation of business processes' information - Brandt, Mariana Baptista [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Pontificia Universidade Catolica Campinas, 2019)
Metadata are considered fundamental elements in Library and Information Science and its and its characteristics, applications and typologies is been studied extensively by researchers in the area, mainly since 2000. This article aims to bring a new typology of metadata to Brazilian Library and Information Science studies, the so-called business metadata. Business metadata are the business context behind data and can be found in any business process in the different sectors of diverse institutions. Considering the lack of literature about this kind of metadata in Library and Information Science, using literature research, this paper aims to bring its concept, applications, examples and studies about business metadata. This research is theoretical and conceptual nature, characterized as exploratory research. Business metadata could be observed as very pertinent to the concepts and principles of Library and Information Science, which allows concluding that this concept can and should be studied by the area, mainly in the studies related to Information Architecture, Information Systems and Information Retrieval.
Keywords: Information Architecture; Enterprise Information; Metadata